PEMANFAATAN GOOGLE MAPS DALAM MEMPROMOSIKAN OBJEK WISATA TEBING MAKARIKI NEGERI YAPUTIH KECAMATAN TEHORU KABUPATEN MALUKU TENGAH - Rahmawati Walalayo; Evandro A.W. Manuputty; August J.R. Ufie (P3M Politeknik Negeri Ambon, 2022)
Makariki Cliffs tourism object is managed by Pokdarwis and has promoted Makariki Cliffs through Facebook and Instagram. But until now, Makariki Cliff has not been